2020
DOI: 10.1002/jsfa.10301
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic degradation of ginkgolic acid by laccase immobilized on novel electrospun nanofiber mat

Abstract: BACKGROUND Ginkgo biloba leaf extract contains many active ingredients that are beneficial for health. However, ginkgolic acid, one of the major components found in G. biloba extract, may cause serious allergic and toxic side effects. The purpose of this study is to immobilize the laccase system on the electrospun nylon fiber mat (NFM) to hydrolyze the ginkgolic acid in G. biloba leaf extract efficiently. RESULTS Novel electrospinning technology successfully produced high‐quality nanoscopic fiber mats made of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…High voltage is applied to a polymer solution and the sample collector to produce electric field jets supporting the formation of fibers through solvent evaporation during the process [222,223]. The use of the technique focuses on the main discussions intrinsically connected with the area; it is interpreted as an innovative, effective technique with low cost and versatility that can be applied in several industrial fields [220,[224][225][226]. The electrified nanofibers have attracted the attention of enzyme engineering and biocatalysis, being considered a potential tool because of their numerous advantages: high surface area, multiple fixation points to the support, high porosity, interconnectivity, high thermal resistance, pH stability, and several solvents [216,220,222,223,227].…”
Section: Electrospinningmentioning
confidence: 99%
See 1 more Smart Citation
“…High voltage is applied to a polymer solution and the sample collector to produce electric field jets supporting the formation of fibers through solvent evaporation during the process [222,223]. The use of the technique focuses on the main discussions intrinsically connected with the area; it is interpreted as an innovative, effective technique with low cost and versatility that can be applied in several industrial fields [220,[224][225][226]. The electrified nanofibers have attracted the attention of enzyme engineering and biocatalysis, being considered a potential tool because of their numerous advantages: high surface area, multiple fixation points to the support, high porosity, interconnectivity, high thermal resistance, pH stability, and several solvents [216,220,222,223,227].…”
Section: Electrospinningmentioning
confidence: 99%
“…Figure 5 shows how the process of enzyme immobilization by electrospinning occurs. Several studies have reported different proposals to immobilize enzymes in electrophile nanofibers [216,219,[223][224][225][226][227][228]. These proposals mainly include binding the enzyme on the surface of nanofibers and enzyme encapsulation [216,219,223,228].…”
Section: Electrospinningmentioning
confidence: 99%
“… 57 64 Laccases have attracted proven interest in biosensing and bioremediation, and they receive increasing attention in biocatalytic synthesis. 57 , 59 , 60 , 62 64 Galactose oxidase finds application in biosensing, production of carbohydrate-based reactive aldehydes, and valorization of hydroxymethylfurfural. 58 , 64 These preliminary results are a promising basis for the application of nonwoven membranes in enzyme technology.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is an effective and versatile method of fabrication from polymer solutions or melted polymer continuous fibers with a diameter ranging from nanometers to micrometers. 1 As a result of a tunable diameter, high porosity and a high specific surface area, electrospun fiber is a suitable candidate for the targeted delivery of labile and sensitive compounds, 2 bioactive encapsulation, 3,4 enzyme immobilization, 5 and nano-sensor 6 and active packaging 7 applications. In recent years, interest in the use of biopolymer electrospun nanofibers for various food applications has increased because of environmental and safety concerns.…”
Section: Introductionmentioning
confidence: 99%